2022
DOI: 10.1186/s12889-022-12843-4
|View full text |Cite
|
Sign up to set email alerts
|

Suicide rate and social environment characteristics in South Korea: the roles of socioeconomic, demographic, urbanicity, general health behaviors, and other environmental factors on suicide rate

Abstract: Background Suicide is a serious worldwide public health concern, and South Korea has shown the highest suicide rate among Organisation for Economic Co-operation and Development (OECD) countries since 2003. Nevertheless, most previous Korean studies on suicide had limitations in investigating various social environment factors using long-term nationwide data. Thus, this study examined how various social environment characteristics are related to the suicide rate at the district-level, using nati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…Moreover, rate of death by suicide per 100,000 population decreased or remained in most OECD countries [ 7 ]. In contrast, in Korea, deaths by suicide increased by 46%, and suicide rates were higher (24.6 per 100,000) than in other countries from 2000 to 2019 [ 9 ]. Additionally, in the United States, suicide rate was a stable period from 2000 to 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rate of death by suicide per 100,000 population decreased or remained in most OECD countries [ 7 ]. In contrast, in Korea, deaths by suicide increased by 46%, and suicide rates were higher (24.6 per 100,000) than in other countries from 2000 to 2019 [ 9 ]. Additionally, in the United States, suicide rate was a stable period from 2000 to 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Jang et al reported that in South Korea, the associations between indices of isolation (% divorce and % detached houses) and suicide rates were stronger for men than for women and for younger age groups than older. 22 Future research is needed to clarify why area-specific suicide risk among young Japanese population is not associated with socioeconomic deprivation, but social fragmentation. Concerning males and females aged 60+ years, suicide risk appeared to be lower in municipalities with higher level of social fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that, only among males aged 0–39 years and females aged 0–39 years and 40–59 years, suicide risk was significantly larger for municipalities in the highest quartile category of social fragmentation. Jang et al reported that in South Korea, the associations between indices of isolation (% divorce and % detached houses) and suicide rates were stronger for men than for women and for younger age groups than older 22. Future research is needed to clarify why area-specific suicide risk among young Japanese population is not associated with socioeconomic deprivation, but social fragmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations